LEARNER MOTIVATION IN ESL LEARNING STRATEGIES AND GENDER ROLE - Prihantoro, Satrio; Widyana, Rahma; Setiawan, Ezra Putranda (LLT Journal: A Journal on Language and Language Teaching, 2018)
Language learning strategy is one of the main factors that help determine how well our students learn a second or foreign language (Oxford, 2003). Research has shown that more effective language learners use more and better learning strategies than poorer language learners (Rubin, 1975; Stern, 1975). This research investigates the difference in ESL learning strategies used by students with different levels of ESL learner motivation and how gender plays a role in both. Strategy Inventory of Language Learning (SILL; Oxford, 1990) and English Language Learner Motivation Scale (ELLMS; Ardasheva, Tong and Tretter, 2012) were used and adopted to measure English language learning strategies and English language learner motivation, by employing 65 male students and 75 female students from Budi Utama Junior High School as participants. The data analyzed showed that there was significant difference in ESL learning strategies used by the students with different levels of ESL learner motivation but there is no significant role of gender in ESL learner motivation and ESL learning strategies.